(untitled) (Journal of Partial Differential Equations, 1989)
The present paper studies a continuous casting problem of two phases: &#8706H(u)&#8706t + b (t) &#8706H(u)&#8706x - &#916u = 0 in &#119967&sup1 (&#937_T) where u is che temperature. H (u) is a maximal monotonic graph. &#937_T = G &#215 (0, T), where G = (0, a) &#215 (0. 1) stands for the ingot. We obtain the existence and the uniqueness of weak solution and the existence of periodic solution for the first boundary problem.